اللجوء الانساني والهجرة غير الشرعية بين سياسة أوروبا ودور ليبيا في مكافحتها : دراسة وصفية تحليلية - عون، كامل محمود أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study deals with the issue of illegal immigration and humanitarian issues in Europe and the North American continent. These two current issues have become more prominent after the outbreak of the Arab Spring. This study examines specifically illegal migration of people from the State of Libya. The researcher also discussed whether the authorities treat migrants and refugees coming from African and Arab countries in accordance with international legislation. The researcher used the inductive method to find the answers as well as using the analytical descriptive approach. The researcher reached several results that indicated the most important factors driving illegal migration are political motives and economic motives as well geographical, demographic, and social factors. The study examined the role of the United Nations, or the lack of it, in ensuring adequate protection of migrant and refugees and the preservation of human rights to those who seek to escape persecution and bloody civil strife.